(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Freedom and Conscience in the Conflict between Humanand Humanistic Dignity Confronted with the practical existence of the human being, theorizing can face great difficulties. This made the discourse about the human being to be as elusive as possible, conciliatory or even alien to reality. Under these new and optimal circumstances, the development of any kind of theories on any topic is unstoppable and even welcomed. Scientists who take the risk of theorizing the practical human being are increasingly scarce. We do not know if we will succeed, but this short paper aims, with the risk of being stigmatized as being unscientific, to address the problem of freedom, conscience, and dignity, in the practical forms of existence of the human being and of the divine Being. We will try to bring out of the diplomatic mothballs the unpolished meanings of human attitudes and aspirations, not aiming for a successful polemic, but in order to recognize the real concerns of human life and to know how insincere we are when, for the sake of scientific discourse, we choose scientific disinformation or, for the sake of diplomatic discourse, we choose the be misinformed regarding the practical needs of life. Under the title Freedom and conscience in the conflict between human and humanistic dignity, we bring to the attention of those interested the legislated realities of the individual (freedom and conscience) and realities that “legislate” the individual (human and humanistic dignity). We avoid scientific politeness and diplomatic discourses, favouring raw information, because the lack of knowledge is not in our highest interest.